COVID-19 and Its Implications to the Assessment of Sustainable Palm Oil Supply Chain Management: An Indonesian Perspective - Hafiz, Nusrat; Azmi, Khairunnisa Mohd; Nimfa, Danjuma Tali; Latiff, Ahmad Shaharudin Abdul; Wahab, Sazali Abd (Frontiers in Sustainability, 2022)
Motivated by the low sustainability index and pressure to meet the global demand for eco-friendly crude palm oil (CPO) in the pandemic-ridden environment, this research aims to investigate the implications of the COVID-19 pandemic to assess the drivers of sustainable supply chain management (SSCM) of the Indonesian CPO sector to tackle supply chain disruptions. To achieve this aim, the study seeks to determine the sustainability drivers to accommodate the pandemic-ridden environment and if sustainability indicators can help improve the supply chain management of the CPO sector. A methodology is divided into two interrelated parts: first, based on a careful review of extant literature of the CPO sector and sustainable supply chain in the light of pandemic. The proposed methodology is then tested using the response data of 108 oil mills’ representatives collected through survey questionnaires and analyzed using statistical tools of reliability, distribution, Kaiser–Meyer–Olkin (KMO), Confirmatory Factor Analysis (CFA), and diagnostic tests of CFA. The findings designate the environmental costs, rapidity, and adaptability as core economic indicators; the social and workforce development, health, and safety workforce development and consumer issues as crucial social indicators; while energy and material efficiency, management of waste and emissions, and sustainable suppliers as the best environmental indicators. This study provides a holistic platform on the implications of the pandemic to assess the SSCM of the CPO sector. These findings are expected to aid the industrial managers in employee skills and health protocols, customer service, and environmental management. The study is also anticipated to guide the supply-chain partners and government policymakers to take initiatives on SSCM in the context of the pandemic.